Protein sequence information encodes more than the global minimum structure - Schwarz, D (2021)
Allostery is a conformational or activity change of a protein’s active site resulting from a binding event at a distant, allosteric, site. The signal transmission is hypothesised to travel via allosteric networks and knowledge about the exact residues that transmit the signal would be beneficial for developing allosteric drugs. Allosteric drugs should offer high selectivity and/or better treatment through combination therapies.